2017
DOI: 10.33899/ijvs.2017.126706
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of urolithiasis crystallodiagnostics

Abstract: Nowadays, one of the most common groups of diseases in veterinary medicine is the urinary system pathology. Urolithiasis is widespread disease, could be found in many species, including cats, dogs, rabbits, guinea-pigs, turtles etc. Despite the large scale of this pathology in animal world, there are some challenges with diagnostic process and diagnosis's verification. The aim of our study is estimation of diagnostic value of advanced urine tesiocrystalloscopy in urolithiasis (by the example of cats). We studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Beberapa tanda klinis urolitiasis pada anjing meliputi ischuria, polakiuria, hemoglobinuria, leukosituria, proteinuria, kristaluria, dan yang paling sering ditemukan adalah hematuria dan dysuria (Martusevich & Kozlova, 2017). Penelitian yang dilaporkan oleh Fromsa dan Saini (2019), dari 23 anjing yang mengalami urolitiasis, hanya tujuh anjing yang ditemukan kristaluria (30.4%).…”
Section: Pendahuluanunclassified
“…Beberapa tanda klinis urolitiasis pada anjing meliputi ischuria, polakiuria, hemoglobinuria, leukosituria, proteinuria, kristaluria, dan yang paling sering ditemukan adalah hematuria dan dysuria (Martusevich & Kozlova, 2017). Penelitian yang dilaporkan oleh Fromsa dan Saini (2019), dari 23 anjing yang mengalami urolitiasis, hanya tujuh anjing yang ditemukan kristaluria (30.4%).…”
Section: Pendahuluanunclassified
“…formation of stones in the urinary tract). Often, CaOxinduced oxidative stress (4,5). As time progresses, we become more aware of what nature contains as beneficial to our health, and with it our desire to learn more about these elements, one of these ancient elements in its existence, which has been talked about in recent research is the Stinging Nettle (Urtica dioica) has been a staple in herbal medicine since ancient times (6).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that dilution of urine has a positive effect on the prevention and treatment of urolithiasis. Dilution of urine helps reduce the concentration of precursors [7,8]. Dilution of urine is achieved by increasing the frequency of diuresis, thereby reducing the residence time of mineral compounds in the bladder.…”
Section: Introductionmentioning
confidence: 99%